POTENSI EKSTRAK DAUN KIRINYUH (Chromolaena odorata L.) TERHADAP PERBAIKAN GAMBARAN HISTOPATOLOGI PERLEMAKAN HATI PADA TIKUS PUTIH (Rattus norvegicus) DENGAN DISLIPIDEMIA SEBUAH SYSTEMATIC LITERATURE REVIEW - Widhi Kusuma Wardhana, (2020)
The prevalence of dyslipidemia sufferers in Indonesia continues to increase. Dyslipidemia can be a risk factor for Non-Alcoholic Fatty Liver (NAFLD). Currently, research has shown that kirinyuh leaf extract can reduce dyslipidemia. However, research on the potential of kirinyuh leaves on the histopathology of NAFLD still needs to be done. The writing of this Systematic Literature Review is expected to identify how the potential of kirinyuh leaf extract (Chromolaena odorata L.) improves the histopathology of fatty liver in albino rats (Rattus norvegicus) with dyslipidemia. Method: Systematic Review by conducting a literature search using Google Scholar and PubMed. Literature that discusses Chromolaena odorata, albino rats, dyslipidemia, and NAFLD. Result: 3 studies concluded that Chromolaena odorata can reduce levels of dyslipidemia in rats. 4 studies concluded that the content of flavonoid can improve the image of NAFLD in albino rats. Conclusion: Chromolaena odorata has the potential to improve the histopathological picture of NAFLD in albino rats with dyslipidemia.